O paradoxo micro-macro da eficácia da ajuda: morto ou vivo? Uma revisão da literatura empírica cross-country - Moreira, Sandrina Berthault (My University, 2005)
O presente trabalho tem um duplo objectivo. Em primeiro lugar, visa dotar o investigador de um quadro-síntese sobre os estudos econométricos que deram relevo à questão da eficácia da ajuda (em termos de crescimentos económico), utilizando uma abordagem cross-country. Esta ferramenta de apoio abrange desde os primeiros estudos realizados na década de setenta até aos últimos desenvolvimentos na área e apresenta uma breve descrição de cada estudo em análise (incluindo principais resultados e conclusões). Como segundo objectivo, este trabalho propõe efectuar uma análise global dos estudos acima referidos e respectivos resultados. Tendo em consideração o quadro teórico e os procedimentos metodológicos e econométricos mais comuns, identificam-se duas gerações de estudos cross-country da relação ajuda-crescimento. Os resultados da primeira geração de estudos, constam com os resultados dos estudos mais recentes, ao não validarem, de forma consciente, o impacto positivo da ajuda no crescimento dos PVD, dando, desta forma, fundamento ao paradoxo micro-macro.

This article has a dual purpose. Firstly, it is intended to provide researchers with an overview of econometric studies that have focussed on the effectiveness of foreign aid (in terms of economic growth) using a cross-country approach. This support tool begins with the first studies conducted in the 1970 sand goes right up to the latest developments in the area, giving a brief description of each study (including its main results and conclusions). These second purpose of this article is to conduct an overall analysis of these studies and their results. Considering the theoretical framework and the most common methodological and econometric procedures I have identified two generations of cross-country studies of the relationship between aid and growth. The results from the first-generation studies differ from those of more recent ones, as they do not consistently validate the positive impact of aid on the growth of developing countries, thus providing grounds for the micro-macro paradox. A reassessment of the results suggests that the statement is excessive, and so, in conjunction with the satisfactory results from second-generation studies, I conclude that the micro-macro paradox no longer makes sense as an outcome of the empirical assessment on aid effectiveness.
The micro-macro paradox of the effectiveness of aid: dead or alive? A survey of the empirical cross-country literature
Keywords: Ajuda internacional; Crescimento económico; Análise entre países; Foreign aid; Economic growth; Cross-country analysis